Malignant Transformation of an Ovarian Endometrioma during Endometriosis Treatment: A Case Report - Hiroaki Takagi; Emi Takata; Jinichi Sakamoto; Satoko Fujita; Masahiro Takakura; Toshiyuki Sasagawa (Hindawi Limited, 2018)
Dienogest (DNG) is considered to be effective against ovarian endometrioma (OMA). We report a rare case of OMA transformation to ovarian cancer during long-term endometriosis treatment with a periodic administration of a gonadotropin-releasing hormone agonist (Gn-RH agonist) and DNG. The patient was a 41-year-old Japanese woman. OMA and adenomyosis of the uterus were revealed via computed tomography. Consequently, she underwent conservative treatment without undergoing surgery because her overall status was poor. She received cyclic therapy (Gn-RH agonist and DNG) for approximately eight years. However, she reported lumbago and underwent close medical examination at our hospital after about eight years of treatment. Under the suspicion of malignant transformation, she underwent surgery. The pathological diagnosis was clear cell carcinoma of the right ovary (stage 2B). After surgery, she received six courses of chemotherapy (conventional TC). No evidence of disease was observed after chemotherapy. Our findings suggest that malignant transformation of OMA can occur during DNG treatment. Since the delayed detection of ovarian cancer greatly affects the prognosis, women older than 40 with OMA are encouraged to undergo regular check-ups every few months.